2021
DOI: 10.4103/jmas.jmas_85_20
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of crural closure for laparoscopic anti-reflux surgeries

Abstract: Background: Long-term dysphagia is a known complication of laparoscopic anti-reflux surgery (LARS). Of the several factors, inadequate hiatal closure is one of the major reasons for its occurrence. The aim of this study is to develop a technique for the quantitative assessment of crural closure during LARS to reduce dysphagia. Materials and Methods: It is an analysis of prospectively collected data of 109 patients who underwent LARS at a tertiary healthcare centre in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, FLIP is not a general inspection tool because it has not yet obtained regulatory approval in Japan and is introduced only in a limited number of facilities. Various attempts have been reported to reduce postoperative dysphagia 11,12 . Aiolfi et al reported that the crura should not be excessively tight to leave a small 5 mm window from the highest stitch to the posterior esophageal wall, 12 but we have experienced severe postoperative dysphagia after LF, so we decided to make an about 1 cm window in Toupet fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…However, FLIP is not a general inspection tool because it has not yet obtained regulatory approval in Japan and is introduced only in a limited number of facilities. Various attempts have been reported to reduce postoperative dysphagia 11,12 . Aiolfi et al reported that the crura should not be excessively tight to leave a small 5 mm window from the highest stitch to the posterior esophageal wall, 12 but we have experienced severe postoperative dysphagia after LF, so we decided to make an about 1 cm window in Toupet fundoplication.…”
Section: Discussionmentioning
confidence: 99%